Yap1 is dispensable for self‐renewal but required for proper differentiation of mouse embryonic stem (ES) cells. (25th February 2016) - Chung, HaeWon; Lee, Bum‐Kyu; Uprety, Nadima; Shen, Wenwen; Lee, Jiwoon; Kim, Jonghwan
Abstract: Yap1 is a transcriptional co‐activator of the Hippo pathway. The importance of Yap1 in early cell fate decision during embryogenesis has been well established, though its role in embryonic stem (ES) cells remains elusive. Here, we report that Yap1 plays crucial roles in normal differentiation rather than self‐renewal of ES cells. Yap1‐depleted ES cells maintain undifferentiated state with a typical colony morphology as well as robust alkaline phosphatase activity. These cells also retain comparable levels of the core pluripotent factors, such as Pou5f1 and Sox2, to the levels in wild‐type ES cells without significant alteration of lineage‐specific marker genes. Conversely, overexpression of Yap1 in ES cells promotes nuclear translocation of Yap1, resulting in disruption of self‐renewal and triggering differentiation by up‐regulating lineage‐specific genes. Moreover, Yap1‐deficient ES cells show impaired induction of lineage markers during differentiation. Collectively, our data demonstrate that Yap1 is a required factor for proper differentiation of mouse ES cells, while remaining dispensable for self‐renewal. Synopsis: Until recently, the roles of Yap1 in mouse embryonic stem (ES) cells have been elusive. This study shows that Yap1 is a critical regulator for proper differentiation but that it is dispensable for self‐renewal of ES cells. Yap1‐depleted ES cells maintain an undifferentiated state. Yap1‐associated factors, Taz and Tead family proteins are not essential for the self‐renewal of ES cells. Yap1 is induced and translocated into the nucleus upon differentiation of ES cells. Yap1 is required for the proper differentiation of ES cells. Abstract : Until recently, the roles of Yap1 in mouse embryonic stem (ES) cells have been elusive. This study shows that Yap1 is a critical regulator for proper differentiation but that it is dispensable for self‐renewal of ES cells.